2009
DOI: 10.1017/s1431927609096421
|View full text |Cite
|
Sign up to set email alerts
|

Making the Invisible Visible: Empowering Pre-college Teachers Through Microscopic Investigations of Micro- and Nano-worlds

Abstract: The microscopic world provides teachers with excellent opportunities to develop hands-on, inquirybased curriculum, yet many K-12 educators lack the knowledge, equipment and skills necessary to engage their students in these types of explorations. Through a Science Education Partnership Award (SEPA) from the National Institutes of Health (NIH), National Center for Research Resources (NCRR), researchers at the University of Southern Maine (USM) are offering professional development activities designed to build s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Building upon successful efforts in cultivation of the viruses shown in Figure 1 from the extreme environments of Kenya's soda lakes (which at pH 11 and above are among the most alkaline on Earth), the USM virology, microbiology and electron microscopy research team has begun to investigate the molecular genetics and the physical and biochemical parameters internal and external to host cells that determine the structural integrity and functionality of viruses in these extreme environments. Parallel research and education efforts in Maine and in Kenya discussed here are expanding the integrated research and education efforts (some reported previously [1,7,8,9]) of the USM Virology and TEM laboratory.…”
mentioning
confidence: 71%
“…Building upon successful efforts in cultivation of the viruses shown in Figure 1 from the extreme environments of Kenya's soda lakes (which at pH 11 and above are among the most alkaline on Earth), the USM virology, microbiology and electron microscopy research team has begun to investigate the molecular genetics and the physical and biochemical parameters internal and external to host cells that determine the structural integrity and functionality of viruses in these extreme environments. Parallel research and education efforts in Maine and in Kenya discussed here are expanding the integrated research and education efforts (some reported previously [1,7,8,9]) of the USM Virology and TEM laboratory.…”
mentioning
confidence: 71%